Mechanobiology in Health and Disease - Verbruggen, Stefaan W. (Elsevier Ltd. : Academic Press, 2018)
Mechanobiology in Health and Disease brings together contributions from leading biologists, clinicians, physicists and engineers in one convenient volume, providing a unified source of information for researchers in this highly multidisciplinary area. Opening chapters provide essential background information on cell mechanotransduction and essential mechanobiology methods and techniques. Other sections focus on the study of mechanobiology in healthy systems, including bone, tendons, muscles, blood vessels, the heart and the skin, as well as mechanobiology studies of pregnancy. Final chapters address the nascent area of mechanobiology in disease, from the study of bone conditions, skin diseases and heart diseases to cancer. A discussion of future perspectives for research completes each chapter in the volume.iA This is a timely resource for both early-career and established researchers working on mechanobiology.